Infatuated with Death; Emily Dickinson and Fadwa Tuqan: A Comparative Study - Daraiseh, Sawsan A.; Aljadallah, Sahar M.; Daraiseh, Banan A. (Dirasat: Human and Social Sciences, 2024)
Objectives: This study conducts a comparative parallel study of the poetry of Dickinson and Tuqan to highlight the interconnectedness of the human experiences in receiving the grand human experience of death, which emerges as a common element despite their differing temporal and spatial contexts. Their poems on death reveal their profound thoughts and perspectives as death permeates into their poems in exceptional and distinctive ways; as a result of the two poets adopting Romanticism as their philosophical framework. Consequently, this study highlights the substancial impact of Romanticism on the development and spread of Comparative Literature. Methods: The study relies on Comparative Literature as its methodology, exploring the historical origins of this field. Initially, Comparative Literature had a Eurocentric focus with racial undertones, but eventually evolved to encompass literature from all nations. The study deals in particular with the topic of “death” in the poetry of Dickinson and Tuqan, as it permeates a significant portion of their poetry, by conducting a parallel comparative analytical study to elucidate and manifest the two poets’ perspectives on the subject of “death”. Additionally, it examines similarities and differences in their views, occasionally drawing from important shared life experiences that profoundly influenced their fascination with death and its prominent presence in their poetry. Results: The death poetry of Dickinson and Tuqan establishes an ideological connection; emphasizing the unity of the human experience despite the differences in temporal, and spatial cons texts, as well cultural and referential frameworks. In their poetry, Death has appeared as an authoritative dictator, a source of wisdom and a shaper of their unique perspectives on love. For Dickinson, love is intertwined with death, while for Tuqan, it represents an escape from it. This is a result of both poets being influenced by aspects of the Romantic movement, therby contributing to the development of comparative studies. Conclusions: Comparative Literature provides a platform that honors literature among nations, enabling its notable dissemination and exchange. Notably, the poetry of Dickinson and Tuqan brings them together through their exploration of death, compelling us to acknowledge and appreciate the shared nature of their most profound human experience and their appreciation of it.